Perancangan UI/UX Aplikasi Forum Diskusi Mahasiswa Universitas Bina Darma Dengan Menerapkan Metode Design Thinking - Dedek Julian; Tata Sutabri; Edi Surya Negara (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2023)
Information on academic activities at Bina Darma University can be obtained via WhatsApp messages to PPM, however, these contacts can only be contacted according to working hours, while students need a medium to exchange information quickly. Student discussion forum applications can meet these needs, where fellow students can exchange information without being limited by time, principal, or semester. The UI/UX design of the student discussion forum application was carried out by applying the Design Thinking method by going through the stages of empathize, define, ideate, prototype, and test. In the design process, gestalt principles are also applied to increase user convenience in using the application. The usability testing results show that 60% of respondents stated that the application was easy to use, while 30% said it was straightforward, and the remaining 10% said it was quite easy to use.